Pakistan - Public Expenditure and Financial Accountability Assessment of Federal Government - World Bank (World Bank, 2012)
This Public Expenditure and Financial Accountability (PEFA) Assessment applies the PEFA framework and methodology to provide a snapshot of the current status of the federal government's public financial management (PFM) system. The report makes no recommendations on policy matters it is specifically concerned with the status of the PFM system and issues relating to financial management processes. It does suggest weaknesses and strengths as well as possible priority areas to take advantage of strengths or to address higher-risk weaknesses. It makes no recommendations, however, on specific measures or action plans. The report provides a basis for these matters to be taken up subsequently, but, consistently with the PEFA framework, they should be subject to a separate discussion during the formulation of a government-led PFM reform agenda. The structure of the PFM performance report is as follows: chapter two gives background information and the country economic, fiscal, and institutional context. Chapter three provides details on each performance indicator (PI) score. Chapter four summarizes the government's ongoing PFM reform programs. Annex one gives a summary of the PEFA assessment; annex two provides sources of information, including a list of documents reviewed and officials consulted; and annex three shows key organizational elements of Pakistan's PFM structure.